2011
DOI: 10.1002/pip.1126
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron‐based microprobe investigation of impurities in raw quartz‐bearing and carbon‐bearing feedstock materials for photovoltaic applications

Abstract: Using synchrotron‐based analytical microprobe techniques, we determine micrometer‐scale elemental composition, spatial distribution, and oxidation state of impurities in raw feedstock materials used in the photovoltaic industry. Investigated Si‐bearing compounds are pegmatitic quartz, hydrothermal quartz, and quartzite. Micrometer‐scale clusters containing Fe, Ti, and/or Ca are frequently observed at structural defects in oxidized states and in bulk concentrations equivalent to inductively coupled plasma mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Interesting results using m-SRXRF spectrometry in the analysis of impurities in raw quartz-bearing and carbon-bearing feedstock materials for photovoltaic applications were found by Bernardis et al 46 These investigations of the silicon-bearing compounds, pegmatitic quartz, hydrothermal quartz and quartzite, showed micro-scale clusters containing oxidised states of Fe, Ti and/or Ca at structural defects. The authors also found that in three carbon-bearing samples, pine wood, pine charcoal and eucalyptus charcoal, clustered metals were only observed in the charcoal samples.…”
Section: Synchrotron and Large Scale Facilitiesmentioning
confidence: 99%
“…Interesting results using m-SRXRF spectrometry in the analysis of impurities in raw quartz-bearing and carbon-bearing feedstock materials for photovoltaic applications were found by Bernardis et al 46 These investigations of the silicon-bearing compounds, pegmatitic quartz, hydrothermal quartz and quartzite, showed micro-scale clusters containing oxidised states of Fe, Ti and/or Ca at structural defects. The authors also found that in three carbon-bearing samples, pine wood, pine charcoal and eucalyptus charcoal, clustered metals were only observed in the charcoal samples.…”
Section: Synchrotron and Large Scale Facilitiesmentioning
confidence: 99%